1999
DOI: 10.1038/sj.bmt.1701756
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of G-CSF effects on hemostasis in allogeneic blood stem cell donors

Abstract: Summary:Granulocyte colony-stimulating factor (G-CSF) is used in healthy donors of peripheral blood stem cells (PBSC) for allogeneic transplantation. However, some data have recently suggested that G-CSF may induce a hypercoagulable state, prompting us to study prospectively 22 PBSC donors before and after G-CSF 5 g/kg twice daily. We sought evidence for changes in the following parameters: platelet count, von Willebrand factor antigen (vWF:Ag) and activity (vWF activity), ␤-thromboglobulin (␤-TG), platelet fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 13 publications
0
46
0
1
Order By: Relevance
“…The mechanism by which rhG-CSF exerts its effects on the endothelium has not been fully explained. Upon activation, neutrophils release reactive oxygen species and intracellular protease that perform several activities on endothelial cells and platelets and may modify the hemostatic balance toward a prothrombotic state, 11,17 to which a series of leukocyte-mediated events may have contributed, in addition to direct toxicity. As we did not investigate the relationship between levels of neutrophil-derived proteases and activation markers, we were not able to demonstrate the role of leukocytemediated endothelial toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which rhG-CSF exerts its effects on the endothelium has not been fully explained. Upon activation, neutrophils release reactive oxygen species and intracellular protease that perform several activities on endothelial cells and platelets and may modify the hemostatic balance toward a prothrombotic state, 11,17 to which a series of leukocyte-mediated events may have contributed, in addition to direct toxicity. As we did not investigate the relationship between levels of neutrophil-derived proteases and activation markers, we were not able to demonstrate the role of leukocytemediated endothelial toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed a decrease in final percentage of ADP induced platelet aggregation whereas Kuroiwa et al showed an increase in platelet aggregation. 4,10 Prophylactic anticoagulation to prevent CAT is not routinely used. Recent studies suggest that thromboprophylaxis with either low-molecular-weight heparin (LMWH) or low-dose warfarin does not prevent symptomatic CAT in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…3 One showed a significant increase in thrombin/antithrombin complex, prothrombin fragment F 1 þ 2 (F1 þ 2), thrombomodulin, factor VIII, von Willebrand factor antigen and activity following G-CSF. 4 Platelet aggregation studies have shown hypercoagulability after G-CSF administration in stem cell donors. The high doses of growth factors used for PBSCM could potentially lead to a hypercoagulable state with increased risk for VTE.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, thrombotic events secondary to enhanced platelet aggregation with an increment in platelet count and development of a hypercoagulable state have been described in patients and donors treated with G-CSF. [53][54][55] Therefore, donors need to be followed carefully, monitoring platelet counts during and after PBSC mobilization and collection procedures. Ethical issues of this technology arise since there are no defined criteria for PBSC donation in children, and safety of the procedure for pediatric donors has not been totally addressed in the literature.…”
Section: Discussionmentioning
confidence: 99%